2002
DOI: 10.1021/jp014552v
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Enhancement for Polymer Langmuir−Blodgett Monolayers Containing Ruthenium Complex by Surface Plasmon Resonance

Abstract: This paper describes effective photocurrent generation based on a polymer Langmuir−Blodgett (LB) monolayer containing ruthenium complex on a silver electrode excited by surface plasmon resonance (SPR). It was found that photocurrent generation is greatly enhanced at an incident angle where the electromagnetic field was most enhanced by SPR. At this angle, the photocurrent is enhanced by a factor of 23.6 compared with that at the critical angle for total internal reflection. The incident monochromatic photon-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Previously, we have found that photocurrent generation based on the polymer LB monolayer containing Ru(bpy) 3 2þ on a silver electrode excited by SPR was enhanced largely compared with far field light irradiation. 90 SPR generation on metal thin film occurs at a critical incident angle of the excitation beam, but, SPR generation on metal nanoparticles requires no special incident angle condition. By far field light irradiation on metal nanoparticle, effective SPR occurs on the surface.…”
Section: Luminescence Enhancement Of Polymer Nano-sheets Under Localimentioning
confidence: 99%
“…Previously, we have found that photocurrent generation based on the polymer LB monolayer containing Ru(bpy) 3 2þ on a silver electrode excited by SPR was enhanced largely compared with far field light irradiation. 90 SPR generation on metal thin film occurs at a critical incident angle of the excitation beam, but, SPR generation on metal nanoparticles requires no special incident angle condition. By far field light irradiation on metal nanoparticle, effective SPR occurs on the surface.…”
Section: Luminescence Enhancement Of Polymer Nano-sheets Under Localimentioning
confidence: 99%
“…As typical examples, electronic excitation of surfaceanchored molecules has been enhanced, as has been verified from the enhancements of fluorescence [1][2][3][4][5][6][7][8] and photocurrent [9][10][11][12] signals. Thus, SPR can offer tremendous advantages in the spectroscopic sensitivity.…”
Section: Introductionmentioning
confidence: 72%
“…Surface plasmon resonance (SPR) measurements were carried out using a homemade apparatus, as described elsewhere. 20 A glass substrate with thermally evaporated gold was used as the deposition substrate for SPR measurements.…”
Section: Methodsmentioning
confidence: 99%